ANALYSIS OF FACTORS DETERMINING WORK ENGAGEMENT OF XYZ COMPANY EMPLOYEES - Silvi Rosiana Suherman; Susi Adiawaty (ESENSI: Jurnal Manajemen Bisnis, 2025)
This study aims to analyze the influencePerceived Organizational Support (POS), Well Being, And Job Satisfaction to Work Engagementon employees of PT. XYZ. This study also aims to determine which variables are most dominant in influencingWork EngagementThe research method used is quantitative and descriptive associative. The research sample consisted of all 70 employees of PT. XYZ, with the sampling technique usingpurposive sampling. The data collection technique was carried out through a questionnaire using a Likert scale of 5. Data analysis usedStructural Equation Modeling(SEM) approachPartial Least Square(PLS) by conducting testingOuter Model, Inner Model, and simultaneous F test. The results of the study show that partially,Perceived Organizational Support(POS) andJob Satisfaction no significant effect to Work Engagement. However, the variablesWell Being have a significant impact to Work Engagement. Simultaneously,Perceived Organizational Support, Well Being, And Job Satisfaction have a significant impact to Work Engagement. The most dominant variable influencingWork Engagement is Well Being.